Design of a tensile-type 3-D multi-scroll chaotic system and its application in secure communication - Jun-peng MA; Li-dan WANG; Shu-kai DUAN; Jie-ning WU (Tongxin xuebao, 2016)
A kind of tensile-type 3-D multi-scroll chaotic attractor based on Chua's circuit was successfully designed. The chaos generation mechanism was studied by analyzing the symmetry and invariance, the existence of the dissipation, as well as the system equilibrium and stability. Then, some basic dynamical properties, such as Lyapunov exponents, fractal dimension, chaotic dynamical behaviors of the new chaotic system were introduced, either numerically or analytically. At the same time, the chaotic circuit of this system was realized by PSPICE. Finally, based on Lyapunov theorem and unidi-rectionally coupled method, the synchronization of the chaotic system has also been investigated. With this approach, the novel system can be applied to secure communication, which can achieve the purpose of covering specific signals. The experimental results are in agreement with numerical simulation results, which verifies the availability and feasibility of this method.